Development E-Module Three Variables Linear Equations System Based On Mathematic Communication - Latifah Rani; Samsul Maarif (Urogram Studi Pendidikan Matematika, Universitas IVET, 2021)
This rapid technological development has a very significant impact on various aspects of human life, one of which is in the aspect of education. The existence of technological developments in the aspect of education gave rise to a new paradigm in which participants acted as constructors in managing the information gained knowledge and educators as facilitators who guide students in learning activities with the aid of an electronic device. However, the use of electronic devices in the form of laptops/computers has not been well implemented to make students passive, and mathematical communication skills are not optimal. Students still consider the material of the Three Variable Linear Equation System to be quite difficult. So, we need innovative learning media in the form of e-modules. The purpose of this study was to develop the contents and find out the quality of e-modules in the material of the Mathematical Communication Based Three Variable Linear Equation System. This research is development research that adapts the ADDIE development model. The results of this study are in the form of an e-module on the material of the Three Variable Linear Equation System based on mathematical communication that can be operated on a laptop/computer offline. The product has been validated by media experts and material experts and gets results in the Good category. The product was also tested on 46 respondents and obtained results in the Good category. Thus, the e-module of the Three Variable Linear Equation System based on mathematical communication is appropriate for use in learning. Keywords: e-module, Linear Equation System of three variables, mathematical communication.